2012
DOI: 10.1371/journal.pgen.1002695
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association for Abdominal Subcutaneous and Visceral Adipose Reveals a Novel Locus for Visceral Fat in Women

Abstract: Body fat distribution, particularly centralized obesity, is associated with metabolic risk above and beyond total adiposity. We performed genome-wide association of abdominal adipose depots quantified using computed tomography (CT) to uncover novel loci for body fat distribution among participants of European ancestry. Subcutaneous and visceral fat were quantified in 5,560 women and 4,997 men from 4 population-based studies. Genome-wide genotyping was performed using standard arrays and imputed to ∼2.5 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
236
6
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(257 citation statements)
references
References 70 publications
11
236
6
4
Order By: Relevance
“…In a large GWAS consisting of 10 557 European individuals, the FTO locus was strongly associated with subcutaneous fat (P ¼ 5.9 Â 10E-08). 36 Relevant to the present report, in a study of 371 adolescents, the rs9939609 FTO SNP was associated with subcutaneous fat in the neck and frontal chest as measured by lipometry. 37 In summary, we found a 680 kb duplication in a subject with extreme obesity and confirmed its presence in multiple family members who were similarly obese and shared an unusual body fat distribution.…”
Section: Discussionsupporting
confidence: 66%
“…In a large GWAS consisting of 10 557 European individuals, the FTO locus was strongly associated with subcutaneous fat (P ¼ 5.9 Â 10E-08). 36 Relevant to the present report, in a study of 371 adolescents, the rs9939609 FTO SNP was associated with subcutaneous fat in the neck and frontal chest as measured by lipometry. 37 In summary, we found a 680 kb duplication in a subject with extreme obesity and confirmed its presence in multiple family members who were similarly obese and shared an unusual body fat distribution.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we investigated whether the 14 recently reported novel waist-hip ratio-associated SNPs 12) and VFA-associated rs1659258 14) also affect VFA or the ratio of VFA to SFA (V/S ratio) in the Japanese population, which is an important factor in the development of metabolic syndrome.…”
Section: Aimmentioning
confidence: 99%
“…(THNSL2) gene was identified to be associated with VFA in women by GWAS for VFA and SFA using CT 14) .…”
mentioning
confidence: 99%
“…Visceral fat is evaluated by waist circumference, waist-hip ratio, bioelectrical impedance, or more precisely, measurement of visceral fat area (VFA) using computed tomography (CT) [1,15]. Numerous studies have shown that VFA is influenced by genetic loci [16][17][18][19][20][21]. However, despite the observation that ADIPOQ is a promising candidate gene for visceral fat accumulation [22,23], few studies have reported a link between ADIPOQ polymorphisms and VFA.…”
Section: Participantsmentioning
confidence: 99%
“…ADIPOQ polymorphisms are associated with insulin resistance in Japanese women Aya Kitamoto 1) , Takuya Kitamoto 1) , Rina So 2) , Tomoaki Matsuo 2) , Yoshio Nakata 2) , Hideyuki Hyogo 3) , Hidenori Ochi 3) , Takahiro Nakamura 4) , Seika Kamohara 5) , Nobuyuki Miyatake 6) , Kazuaki Kotani 7) , Ikuo Mineo 8) , Jun Wada 9) , Yuji Ogawa 10) , Masato Yoneda 10) , Atsushi Nakajima 10) , Tohru Funahashi 11) , Shigeru Miyazaki 12) , Katsuto Tokunaga 13) , Hiroaki Masuzaki 14) , Takato Ueno 15) , Kazuaki Chayama 3) , Kazuyuki Hamaguchi 16) , Kentaro Yamada 17) , Toshiaki Hanafusa 18) , Shinichi Oikawa 19) , Toshiie Sakata 20) , Kiyoji Tanaka 2) , Yuji Matsuzawa 7) and Kikuko Hotta 1)…”
unclassified